STUDY OF THE MAIN RISK FACTORS OF DYSMETABOLISM IN CHILDREN OF PUBERT AGE (American Journal of Pedagogical and Educational Research, 2023)
Currently, obesity is one of the urgent problems of clinical medicine. More than 1 million people in the world are overweight, and of these, 300 million are obese. Children with obesity suffer from various diseases much more often than children with normal weight. 55 children of pubertal age, patients with exogenous constitutional obesity and arterial hypertension were examined. Risk factors for the development of dysmetabolism in children have been identified. A relationship has been established between BMI, lipid and carbohydrate metabolism indicators with previously identified risk factors, as well as an inverse correlation between birth weight and BMI. These facts characterize low birth weight as a significant risk factor for the development of obesity and subsequent metabolic syndrome.